Memórias do CAPe: História e representação estudantil do Centro Acadêmico de Pedagogia da Universidade do Amazonas em tempos de Ditadura, 1980-1983 - Souza, Flávia Eugênia Rodrigues de (Brasil, 2024)
This article, developed within the field of history of education, aims to reconstruct the history of the Academic Center of Pedagogy (CAPe) of the University of Amazonas (UA), future Federal University of Amazonas (UFAM), from specific bibliography, official documents from the National Information Service (SNI) and memories of people linked to student representation in the period. We also aim to study the structure of the students' political activity within the UA and to know the memories of some of the CAPe members in the period, frequently cited in the confidential dossiers of the SNI. The methodology markedly used in this research is that of Oral History, linked to the category of memory analysis, considering that our main sources are interviews with people who were involved with student representation during the dictatorship. As a result, we brought to light the past of this student representation in the face of repression and censorship, stimulating the political and critical activity of the new generations of university students, in addition to providing the UFAM academic community with knowledge about its own past.